2012
DOI: 10.1128/jvi.00602-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Endogenous Retroviral Elements in the Blood of HIV-1-Infected Individuals

Abstract: We previously reported finding the RNA of a type K human endogenous retrovirus, HERV-K (HML-2), at high titers in the plasma of HIV-1-infected and cancer patients (R. Contreras-Galindo et al., J. Virol. 82:9329 -9236, 2008.). The extent to which the HERV-K (HML-2) proviruses become activated and the nature of their activated viral RNAs remain important questions. Therefore, we amplified and sequenced the full-length RNA of the env gene of the type 1 and 2 HERV-K (HML-2) viruses collected from the plasma of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
135
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(147 citation statements)
references
References 46 publications
7
135
1
1
Order By: Relevance
“…Furthermore, upregulation of HERV-K RNA was detected (14-17, 19, 40) in plasma samples of HIV-1-infected individuals, in HIV-1-infected T cells (17,38), and in HIV-1 Tat-transfected T cells (23). In addition to RNA, HERV-K Gag proteins were also observed to increase upon HIV-1 infection (15,17) and HIV-1 Tat transfection (23). These reports collectively suggest that HIV-1 infection enhances the HERV-K expression in T cells.…”
mentioning
confidence: 87%
“…Furthermore, upregulation of HERV-K RNA was detected (14-17, 19, 40) in plasma samples of HIV-1-infected individuals, in HIV-1-infected T cells (17,38), and in HIV-1 Tat-transfected T cells (23). In addition to RNA, HERV-K Gag proteins were also observed to increase upon HIV-1 infection (15,17) and HIV-1 Tat transfection (23). These reports collectively suggest that HIV-1 infection enhances the HERV-K expression in T cells.…”
mentioning
confidence: 87%
“…Analysis of the HERV-K (HML-2) long terminal repeats (LTRs) for mutations and deletions was performed using published sequences (9,45). Potential transcription factor binding sites were analyzed using the online prediction software tools ALGGEN PROMO and version 8.3 of TRANSFAC (BioBase Co., Beverly, MA) (71,72).…”
Section: Addition Of Exogenous Tat Proteinmentioning
confidence: 99%
“…It appears that expression depends upon individual host factors, like ethnicity (10,21,22,24), cell populations (18,25,26), and tissue types (27)(28)(29). Additionally, external stimuli, such as infections, viral transactivators, chemical exposures, cytokines, hormones, and inflammation, can induce expression of these proviruses (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). We and others have shown that HIV-1 infection is associated with increased HERV-K (HML-2) expression in vitro and in vivo (33,(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
mentioning
confidence: 99%
See 2 more Smart Citations